MINDFULNESS DALAM KOMUNIKASI ANTARBUDAYA (Studi Deskriptif pada Peserta Indonesia – Poland Cross-Cultural Program) - Durrotul Mas’udah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
Culture and communication are inseparable. Since different cultures provide different norms, values, and rules, people from different cultures are likely to communicate in different manner. Gudykunst argued that communication between people from different cultures is thwarted by anxiety and uncertainty. He believed that mindfulness is the moderate process to manage those anxiety and uncertainty perceived by those strangers and in-group members. Indonesia – Poland Cross-Cultural Program (IPCCP) was designed to confront two Indonesians and seven Poles in such intercultural encounter. Since they come from different cultural backgrounds, several differences arose. Those differences sometimes emerged anxiety and uncertainty.By applying Gudykunst’s Anxiety/ Uncertainty Management Theory (AUM Theory), this research is aimed to examine what kinds of anxiety and uncertainty perceived by those Indonesians and Poles, as well as what kinds of effort they had done to mindfully manage those problems. To enrich the analysis of mindfulness, the researcher also applies Langer’s three characteristics of mindfulness and Jandt’s four competencies in mindful intercultural communication. This research reveals that both Indonesians and Poles had mindfully managed their anxiety and uncertainty by implementing five efforts, which are: bringing motivations into actions, self-disclosure, understanding differences, perceiving similarities, and building personal closeness.